2018
DOI: 10.3390/app8101710
|View full text |Cite
|
Sign up to set email alerts
|

FOG De-Noising Algorithm Based on Augmented Nonlinear Differentiator and Singular Spectrum Analysis

Abstract: A novel algorithm based on singular spectrum analysis (SSA) and augmented nonlinear differentiator (AND) for extracting the useful signal from a noisy measurement of fiber optic gyroscope (FOG) is proposed in this paper. As a novel type of tracking differentiator, augmented nonlinear differentiator (AND) has the advantages of dynamical performance and noise-attenuation ability. However, there is a contradiction in AND, i.e., selecting a larger acceleration factor may cause faster convergence but bad random noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Hence, CC is used here as a determination criterion for each R of STD. The steps of VMD-STD algorithm are given below [21].…”
Section: Problem Formulation and Innovation Solutionmentioning
confidence: 99%
“…Hence, CC is used here as a determination criterion for each R of STD. The steps of VMD-STD algorithm are given below [21].…”
Section: Problem Formulation and Innovation Solutionmentioning
confidence: 99%
“…The Allan variance analysis results indicated that the Q, N, and B reduced from 12.915 to 2.429 × 10 −1 , 1.8 × 10 −2 to 5.061 × 10 −4 , and 3.01 × 10 −1 to 1 × 10 −2 based on the X axis; from 7.680 to 1.38 × 10 −1 , 1.2 × 10 −2 to 2.647 × 10 −4 , and 1.72 × 10 −1 to 6 × 10 −3 based on the Y axis; and from 7.093 to 1.25 × 10 −1 , 1 × 10 −2 to Micromachines 2023, 14, 1712 3 of 18 1.549 × 10 −4 , and 1.53 × 10 −1 to 7 × 10 −3 based on the X axis, respectively. Zhang et al [20] proposed a novel algorithm based on singular spectrum analysis (SSA) and augmented nonlinear differentiator (AND) to extract the useful signal from a noisy measurement of FOGs. The proposed SSA-AND algorithm has a better denoising ability compared with other advanced denoising algorithms, and the temperature drift of the FOG can be extracted effectively without signal delay.…”
Section: Introductionmentioning
confidence: 99%
“…That is chattering of system output due to the numerical error caused by inappropriate discretization of the discontinuous signum function [28], [29]. In order to attenuate chattering, some methods such as boundary layer [30], [31], continuous function [10], [11], adaptive switching gain [32], and high order sliding mode [5], [12] are applied. However, these methods reduce or avoid chattering by loosing the inherent characteristics of sliding mode technique in a strict mathematical sense.…”
Section: Introductionmentioning
confidence: 99%